Perancangan Sistem Pakar Diagnosis Tingkat Stres Pada Siswa Korban Bullying Menggunakan Metode Forward Chaining (Studi Kasus: SMK Triguna Utama) - Ahmad Rifa`i; Lely Panca Andriyanto (CV. Multi Kreasi Media, 2025)
Advances in technology have encouraged the development of web-based expert systems to help diagnose stress levels in students who are victims of bullying. This study aims to develop and build an expert system that can overcome the difficulties in manually identifying students' stress levels at SMK Triguna Utama. Manual processes so far often face problems such as inconsistent results and lack of clear data. The system is designed using the forward chaining method, which works by analyzing stress symptoms based on the data entered. Data for the system was collected through questionnaires filled out by students. The findings of this research are expected to assist schools understand students' conditions better, provide accurate information, and help make decisions to provide assistance to students. This system is expected to support efforts to improve students' mental health at SMK Triguna Utama and other schools.